Posthumous Acknowledgement Dr. Hernando Artemio Criollo Escobar Editor in chief of the Revista de Ciencias Agrícolas - Lagos, Tulio César (Revista de Ciencias Agrícolas, 2020)
“Death is the beginning of a love story that we will live eternally with God and with the people we love. Many people die daily in the world, but those who by their works transcend and reconcile us with humanity are few”. Dr. HERNANDO ARTEMIO CRIOLLO ESCOBAR, was a member of the Editorial Team and Editorin-Chief of the Revista de Ciencias Agrícolas, he stood out for his commitment to editorial duties, showing responsibility, intelligence, great interpersonal and teamwork skills, always concerned with scientific research. He founded the research group of Andean Fruit plants, through his twenty years of academic and scientific life he promoted the social and economic development of the agriculture and also the higher education in the department of Nariño, Colombia.